Regulation And Institutional Arrangement Of Village-Owned Enterprises After The Work Creation Era Applied - Rahmat Teguh Santoso Gobel; Mohamad Hidayat Muhtar; Viorizza Suciani Putri (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The management of BUMDesa is not yet optimal because many BUMDesa administrators still need to understand BUMDesa regulations and institutions. Seeing these problems, there needs to be capacity building preceded by legal reasons as a guideline for regulating BUMDesa management signs. Increasing the capacity of Village-Owned Enterprises (BUMDesa) as an organ driving the village economy can be carried out through the Job Creation Era, which has become a momentum for structuring BUMDesa regulations and institutions. The era of work creation referred to is the birth of Law Number 11 of 2020 concerning Job Creation which is now declared invalid with the presence of Government Regulation  (Perpu) Number 2 of 2022 concerning Job Creation. This study uses normative legal research methods(normative legal research). The author uses this legal research because the focus is on studying literature and laws and regulations related to the object of research. The results of the research show that the Job Creation Perpu needs to be pushed into law so that it can become a legal umbrella for the establishment and management of BUMDesa institutions because, in fact, the spirit that is carried out in the Job Creation Era, namely improving the investment ecosystem and business activities, one of them through the institutional arrangement of BUM Desa.